Vertebrobasilar ischemia and hemorrhage : clinical findings, diagnosis and management of posterior circulation disease - Caplan, Louis R. (Cambridge : Cambridge University Press, 2015)
This comprehensive review of vascular disease in the vertebrobasilar circulation is based on Dr Louis R. Caplan's extensive experience and observation of patients from the New England Medical Center posterior circulation stroke registry. It benefits from an organized, uniform, and coherent analysis of all types of vascular disease involving the posterior circulation, presented by a single author who is one of the world's leading authorities on this topic. This new edition is fully updated throughout, including a review of all the literature published on this topic since the previous edition in 1996. There are major rewrites for the chapters on diagnosis and therapy, inclusion of modern imaging techniques, and extensive illustrations. Essential reading for stroke physicians and neurologists, the book will also be an important source of reference for neurosurgeons, vascular surgeons and endovascular radiologists.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Cerebrovascular disorders; Cerebrovascular circulation; Vertebrobasilar Insufficiency